Steroid Stewardship in COVID-19 - Shrestha, Gentle Sunder; Rimal, Ankit (Journal of Nepal Health Research Council, 2021)
Corticosteroids have transformed clinical practice in COVID-19 following the publication of the results of the RECOVERY trial. Despite available evidence, there is considerable disparity among physicians in the dose and duration of steroids they prescribe. Steroids have a fragile affiliation in clinical practice with the benefits frequently accompanied by distressing adverse effects. An institutional steroid stewardship program can help all physicians take advantage of what is the only proven therapy of benefit in this global crisis while avoiding its overuse and the numerous adverse effects associated with it.Keywords: COVID-19; corticosteroids; RECOVERY trial; steroid stewardship